DISTANCE EDUCATION: A PROGRAM TO ACCOMMODATE DIVERSE CHILDREN WITH DISABILITIES (Proceedings of International Conference on Special Education, 2017)
Distance Education (DisEd) Program for Children with Disabilities (CWD) is a Special Education (SPED) program initiated and implemented in Nantangalan Elementary School SPED Center, Pozorrubio, Pangasinan. Philippines. It is designed to accommodate all types of learners with diversity in disabilities, values and status in the community. It helps these learners access to education through an alternative delivery mode called Homebound Instruction. It provides intervention to help develop the language, cognitive, motor, socialization and self-help skills of its learners. It supports the “No Left Behind” and “Zero Reject” policies, the Education for All program of the Philippine government and the Inclusive Education program of the Department of Education. It is a strategy to increase the Participation Rate of the school. The learnerss of this program were those learners with chronic illness ages 9 to 21 years old. They were bed-ridden and with difficulty in mobility which hinder them to go to school and learn. The Portage Guide to Early Education checklist in evaluating the initial, progress and final performance of the learners with the direct observation, parents’ testimony, interview checklists were used to gather data as the research methodology. Findings revealed that learners’ skills had improved. Learners were found to be cooperative and active with their teacher. There was transformation in their faces from sadness to happiness. To conclude, DisEd accommodates all types of learners regardless of their disability, differences and diversity. It makes learning achievable in accordance with the learner’s pace of learning. Inclusion for the bed-ridden learners in the regular class/school is possible. Parents of the learners were benefited from this program. Linkages with and among education stakeholders was strengthened.